Working Capital Management and the Profitability of Commercial Banks: A Case Study of Equity Bank Mukono Branch - Devota Izabayo (Uganda Christian University, 2026)
This research paper has analysed how the working capital can be managed to ensure that commercial banks make higher profits, using Equity Bank Mukono Branch as the case study. The study examined particularly the effects of cash and liquid-asset management, receivables management, and payables/funding structure on the financial performance of the branch in terms of Return on Assets (ROA), Return on Equity (ROE) and Net Interest Margin (NIM). Research design used was descriptive cross-sectional research design which involved quantitative and qualitative research approaches. The target population consisted of 50 employees with a representative sample of 44 employees being chosen as a combination of simple random and purposive sampling methods. The data were gathered using structured questionnaires and by interviewing key officials within the banks and analyzed using descriptive statistics, Pearson correlation and a regression analysis and thematic qualitative analysis. The results indicated that working capital management elements had significant and positive impacts on the profitability of the bank. The greatest impact was on receivables management where regular follow-ups on the loan repayment and effective collection procedures improved cash flows and minimized bad loans. Management of cash and liquid assets was also very high which maintained the best liquidity status as well as efficiency in operations and minimal idle funds. Equally, payables and funding structure influenced financial performance positively as it minimized the liquidity risks and maximized the financing costs. The paper concluded that a working capital management system, which handles cash, receivables and payables in a coordinated manner is important in ensuring profitability maximization and competitive edge in the banking industry. On the basis of these findings, some of the recommendations are the strengthening of the cash and liquidity monitoring using automated system, improvement of credit risk assessment and receivables management, optimization of payables and funding strategy and alignment of internal policies with the best practice in working capital management. The research also recommends the future study of the contribution of technological advances, including artificial intelligence and blockchain, and the impact of external economic forces on the working capital management effectiveness of Ugandan banks.
Undergraduate research